Single‐center implementation of endoscopic submucosal dissection (ESD) in the colorectum: Low recurrence rate after intention‐to‐treat ESD. Issue 3 (3rd January 2018) - Wagner, Andrej; Neureiter, Daniel; Kiesslich, Tobias; Wolkersdörfer, Gernot W.; Pleininger, Thomas; Mayr, Christian; Dienhart, Christiane; Yahagi, Naohisa; Oyama, Tsuneo; Berr, Frieder
Abstract : Background and Aim: Colorectal endoscopic submucosal dissection (ESD) shows higher R0 resection and lower local recurrence rates than endoscopic mucosal resection (EMR) in Japan. In Europe, independent learning of ESD in the colorectum is feasible, but yet to be analyzed for curative resection and recurrence rates. Methods: After experimental training under supervision by Japanese experts (T.O., N.Y.), three endoscopists independently carried out 83 ESD procedures intention‐to‐treat for lesions in the entire colorectum of 67 patients in a prospective registry (November 2009 to June 2016). Results: ESD was feasible in 80 (96%) colorectal neoplasias (mean diameter 33.6 [± 1.8] mm), and three more required conversion to piecemeal EMR. The lesions were adenomas in 66% with low‐grade intraepithelial neoplasia (LGIN), 29% with high‐grade intraepithelial neoplasia, and 5% with carcinomas (G2, pT1). ESD had to be facilitated by the final use of snaring (hybrid‐ESD, n = 45), especially in the initial learning period. En‐bloc resection rate was 85%. Complications were microperforations (7%, conducive to one hemicolectomy), and delayed bleeding (1%) without mortality or long‐term morbidity. Residual adenomas with LGIN (5%) after hybrid‐ESD did not recur after endoscopic ablation. All malignant neoplasias (34%) were curatively resected without recurrence after a mean follow up of 19.5 (± 3.2) months. Conclusions: During independent ESD learning in the colorectum, ESD intention‐to‐treat showed a low recurrence rate after appropriate training, and hybrid‐ESD showed acceptable complication and recurrence rates, justifying hybrid‐ESD as a strategy for self‐completion and rescue.